2023 Indonesian Guidelines for Heart Failure Treatment: Working Group on Heart Failure and Cardiometabolic Diseases, Indonesian Heart Association - Hasanah, Dian Yaniarti; Zulkarnain, Edrian; Arifianto, Habibie; Prameswari, Hawani Sasmaya; Suciadi, Leonardo Paskah; Yamin, Paskariatne Probo Dewi; Pratikto, Rarsari Soerarso; Nauli, Siti Elkana; Putri, Vebiona Kartini Prima; Soedarsono, Wahyu Aditya; Sarastri, Yuke (Jurnal Kardiologi Indonesia, 2024)
Heart failure is a health problem with high mortality and morbidity rates in developed and developing countries such as Indonesia. The prevalence of heart failure itself is increasing because patients who experience acute heart failure can progress to chronic heart failure. Guidelines-Directed Medical Therapy (GDMT) with recommended doses is still underutilized in heart failure patients with reduced ejection fraction (HFrEF). In Indonesia itself, even though it has a fairly high rate of use of ACE-inhibitors (ACE-I) or angiotensin receptor blockers (ARB), Indonesia has the lowest rate of use of β-blockers and aldosterone inhibitors (also called Mineralocorticoid Receptor Antagonists, MRA) of the entire ASIAN-HF registry.84 Therefore, the writing of this guideline was carried out as an effort to provide practical guidance regarding the diagnosis, assessment and management of acute and chronic heart failure. Thus, it is hoped that efforts can be made to prevent the increase in prevalence and reduce the number of rehospitalization with complete management. This book was written as an update to the 2020 Guideline for the Management of Heart Failure: Indonesian Heart Association. The sources of our updates came from many references and literatures carried out by each contributor and reviewed by EBM team.